French language learning strategies among mobility students - Phang, Xin Huey; Abdul Halim, Hazlina (2015)
This paper aims to investigate the French language learning strategies by mobility students in France by using Oxford (1990b) taxonomy of language learning strategies. The respondents of the study were 5 mobility students from different countries, aged between 19 to 23 years old and studied in France. The instrument used for this research were interviews, and a series of probes to evoke the respondents’ responses concerning learning strategies’ thoughts and feelings about their experiences. The Daily Interpretive Analysis (DIA) was used to analyse the results. It was found that the strategies which were used the most among the mobility students are memory-related strategies to help them to remember certain vocabularies. Besides that, the respondents pointed out that social strategy is beneficial for them to faster achieve the learning goals. It is hoped that this research will provide information about of the use of language learning strategies, which will enhance French learning for non-native learners. Further, the better understanding of language learning strategies for French teachers can help students to learn more successfully and develop their learning autonomy. To this end, this paper can also serve as a research reference in the field of language learning strategies, particularly the relationship between language learning and the mobility students in France.